Order of treatment matters in ischemic stroke: mechanical thrombectomy first, then carotid artery stenting for tandem lesions of the anterior circulation - Maus, Volker; Möhlenbruch, Markus Alfred (Cerebrovascular diseases, 2018)
Background: One endovascular treatment option of acute ischemic stroke due to tandem occlusion (TO) comprises intracranial thrombectomy and acute extracranial carotid artery stenting (CAS). In this setting, the order of treatment may impact the clinical outcome in this stroke subtype. Methods: Retrospective analysis was performed on data prospectively collected in 4 international stroke centers between 2013 and 2017. One hundred sixty-five patients with anterior TO were treated by endovascular therapy. Clinical and procedural data were evaluated. Favorable clinical outcome was defined as modified Rankin Scale (mRS) ≤2 at 90 days. Propensity score matching was performed for different treatment strategies. Results: Patients’ mean age was 65 ± 11 years and 118 were male (69%). The median admission National Institutes of Health Stroke Scale was 15 (interquartile range 8). In 59% of the patients (n = 101), the antegrade strategy (first stenting, then thrombectomy) was performed, in 41% (n = 70) retrograde treatment (first thrombectomy, then stenting). Successful reperfusion (mTICI ≥2b) was achieved in 128 patients (75%). Fifty-nine patients (39%) showed a favorable clinical outcome after 90 days. After propensity score matching, data of 100 patients could be analyzed. Analysis revealed that the retrograde strategy yielded a significantly higher rate of successful reperfusion compared to the antegrade strategy (92 vs. 56%; p < 0.001). The rate of favorable clinical outcome after 90 days (mRS ≤2) was consistently higher (44 vs. 30%; p < 0.05) in the retrograde strategy group. Conclusion: Mechanical thrombectomy prior to acute CAS in TO is a predictive factor for favorable clinical outcome at 90 days.
Gesehen am 18.10.2019